2001
DOI: 10.1182/blood.v97.6.1727
|View full text |Cite
|
Sign up to set email alerts
|

Platelet endothelial cell adhesion molecule-1 serves as an inhibitory receptor that modulates platelet responses to collagen

Abstract: Platelet responses to collagen are mediated by the combined actions of the integrin ␣ 2 ␤ 1 , which serves as a major collagenbinding receptor, and the GPVI/FcR␥-chain complex, which transmits collagen-specific activation signals into the cell interior through the action of an immunoreceptor tyrosine-based activation motif within the cytoplasmic domain of the FcR␥-chain. Despite much progress in identifying components of the signaling pathway responsible for collagen-induced platelet activation, virtually noth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
133
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 68 publications
(50 reference statements)
11
133
0
1
Order By: Relevance
“…1,2 The subtle phenotype was most evident at concentrations of collagen at 1 g/mL but was not so evident at higher concentrations of collagen 10 to 30 g/mL. This was also the case using CRP as the GPVI-selective agonist.…”
Section: Ceacam1 Modulates Platelet-collagen Interactions 1825mentioning
confidence: 65%
See 2 more Smart Citations
“…1,2 The subtle phenotype was most evident at concentrations of collagen at 1 g/mL but was not so evident at higher concentrations of collagen 10 to 30 g/mL. This was also the case using CRP as the GPVI-selective agonist.…”
Section: Ceacam1 Modulates Platelet-collagen Interactions 1825mentioning
confidence: 65%
“…1,2 However, based on several studies, it would appear that platelets contain multiple Ig-ITIM superfamily members that are likely to have a modulatory role in regulating platelet-collagen interactions. Several reports suggest that platelets contain other Ig-ITIM superfamily members, including G6B and TREM (triggering receptors expressed on myeloid cells)-like transcript-1 (TLT-1), that may attenuate platelet function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In platelets, PECAM‐1 is present both in alpha granules as well as on the platelet plasma membrane 34. In endothelial cells, the molecule is located on the plasma membrane and is concentrated at endothelial cell‐cell junctions.…”
Section: Discussionmentioning
confidence: 99%
“…PECAM‐1 has been shown to have proinflammatory activity through the promotion of leukocyte‐endothelial translocation and transmission of systemic signals associated with endothelial stress 37. Unlike platelet P‐selectin, which supports neutrophil‐platelet and platelet‐endothelial interactions, platelet PECAM is an inhibitory molecule that has been proposed to limit thrombus formation by limiting platelet‐platelet interactions as well as platelet adhesion to collagen 34, 38, 39. These studies have suggested that PECAM‐1 serves to regulate thrombus formation and thereby inhibit vessel occlusion.…”
Section: Discussionmentioning
confidence: 99%